INFLUENCE OF FOREIGN FABRIC DOMINANCE ON THE CULTURAL DESIGN OF MALAYSIAN ARTIFACTS - Xuan Zhen, Sarah Wahida Hasbullah, (Chelonian Research Foundation, 2023)
To develop into a modern, diversified, and free market, Malaysia has kept rapid and inclusive economic development, along with real GDP, at a substantial 6.4% annually since 1970. Malaysia as a country has always put efforts to build its image by establishing economic partnerships with many countries across the globe. Trading between Malaysia and other foreign countries has not only affected the cultural art design of artifacts but also has changed the tourism industry. A literature review guided this study and the results indicated that foreign fabrics have both positive and negative aspects when it comes to Malaysian cultural artifacts. Foreign fabrics have increased the creativity and improvement of local textile industries in designing various materials for Malaysians to meet customer needs in the current competitive business economy. However, the long-term result is that the cultural designs of Malaysia are likely to get extinct. As a result, the article recommends that the local textile industries should design textile materials that accommodate both foreign (modern) and indigenous fabrics to avoid losing Malaysian identity. Keywords: embroidery, foreign fabric, culture, artifacts, Malaysia